Comparing the effect of different levels of zinc hydroxychloride with inorganic zinc sulfate on in vitro rumen fermentation parameters - Pal, Ravi Prakash; Mani, Veena; Sarkar, Srobana; Mir, Shahid Hassan; Sharma, Amit; Sharma, Hunny (Indian Journal of Dairy Science, 2020)
Optimum productivity in ruminants is positively related to efficient rumen fermentation. Apart from major nutrients in diet, micronutrients (trace elements and vitamin B complex) play an essential role in maintaining proper rumen function; however the effect depends on source and level of micronutrients supplementation.Therefore, present study was conducted to compare the effects of different sources of hydroxy and inorganic zinc on in vitro rumen fermentation parameters. Different levels (0, 40, 80, and 160 ppm) of Zn as hydroxy zinc chloride (Zn5(OH)8Cl2) and inorganic zinc sulfate (ZnSO4) were added in substrate consisting of roughage (sugargraze fodder; a cross of sorghum and maize) and concentrate mixture in the ratio 50:50. Inclusion of Zn as zinc hydroxychloride and ZnSO4 at different levels showed no change in total gas (mL/g DM) production. Similarly, supplementation of zinc either as zinc hydroxychloide or ZnSO4 upto160 ppm supplementation did not affect (P>0.05) in vitro dry matter and organic matter digestibility (%) of the diet. Furthermore, no significant effect was observed in the CH4 (%, mL/24h and mL/100mg DM) and NH3-N (mg/dL) and individual fatty acid concentrations with variable sources and levels of Zn supplementation. It can be concluded from the present findings that supplementation of both hydroxy Zn and inorganic Zn up to 160 ppm had no adverse effect on in vitro rumen fermentation. Hence, hydroxy Zn can be used as an alternative source of Zn in the diet of ruminants to conventional inorganic sources.